2015
DOI: 10.1007/s11920-015-0554-4
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances as an Evidence-Based Suicide Risk Factor

Abstract: Increasing research indicates that sleep disturbances may confer increased risk for suicidal behaviors, including suicidal ideation, suicide attempts, and death by suicide. Despite increased investigation, a number of methodological problems present important limitations to the validity and generalizability of findings in this area, which warrant additional focus. To evaluate and delineate sleep disturbances as an evidence-based suicide risk factor, a systematic review of the extant literature was conducted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
228
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 333 publications
(254 citation statements)
references
References 30 publications
17
228
1
8
Order By: Relevance
“…Our findings also add to the growing body of literature supporting the relationship between insomnia severity and suicidal ideation 6,7,19 and, additionally, extend prior work by suggesting that sleep disturbances contribute to increased suicidal desire by reducing one's feelings of connectedness with others. This both aligns and contrasts with findings from prior studies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our findings also add to the growing body of literature supporting the relationship between insomnia severity and suicidal ideation 6,7,19 and, additionally, extend prior work by suggesting that sleep disturbances contribute to increased suicidal desire by reducing one's feelings of connectedness with others. This both aligns and contrasts with findings from prior studies.…”
Section: Discussionsupporting
confidence: 81%
“…6,7 A number of studies have demonstrated that insomnia is strongly associated with suicidal ideation cross-sectionally 8,9,10 and longitudinally, 11,12 even when controlling for hopelessness and depression. 13 Furthermore, several studies have established a link between insomnia and death by suicide among adolescents, 14 adults, 15 and older adults, 16 underscoring insomnia as a critical risk factor for suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Gegenwärtig genügen nur wenige dieser Studien methodisch evidenzbasierten Ansprüchen [16]. Auch beziehen sich die meisten Studien nur auf subjektive Einschätzungen von Schlaf und Schlafparametern ohne apparative Daten (Polysomnografien: [2,36,52,97]).…”
Section: Methodeunclassified
“…Die vorgestellten Studien belegen -trotz ihrer Heterogenität, methodischen Einschränkungen und der zugrunde liegenden Problematik der überlappenden Syndrome Schlafstörungen und Suizidalität und ihrer beider Häufigkeiten bei psychischen Erkrankungen -umfänglich die potenzielle Bedeutung von Schlafmangel und Schlafstörungen als Risikofaktoren für Suizidalität [16] und den hohen klinischen Stellenwert von Schlafstörun-gen bei der Suizidalitätseinschätzung und Suizidprävention [15,72,82,87]. Auch in einer jüngst erschienen ersten Metaanalyse über knapp 150.000 Individuen [17] konnte gezeigt werden, dass Schlafstö-rungenmiterhöhtem relativem Risikofür Suizidgedanken, Suizidpläne und -ver- [87], legt nahe, Schlafstörungen als unabhän-gigen Risikofaktor für Suizidalität anzuerkennen.…”
Section: Diskussionunclassified
See 1 more Smart Citation